"Kri ni voda" - Knežević Hočevar, Duška (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2004)
The contribution discusses various construction of collective belonging of the'descendants of the Uskoki' from the regions of Bela Krajina and south-western Žumberk in Croatia, which was conditioned for different social actors by the changes of political status of the border between Slovenia and Croatia. Both from the perspective of the 'Slovenian state' and the inhabitants who live in the border area, the change of the Slovene-Croatian border regime from an international to the Schengen one is especially significant because it formed a specific understanding of previous and currentborder regimes and the 'situation of the borderlanders'. The inhabitants of the border region who where of non-Slovenian origin were thus suddenly, immediately before and after the declaration of Slovenian independence in 1991, 'discovered' in the public debates as descendants of theUskoki, who could - due to their presumed unconditional loyalty to their non-Slovenian origin - create conditions for an 'ethnic conflict' in Slovenia.The author thus examines two views on the implementation of 'appropriate measures' along the Slovene-Croatian border. On the one hand, sheexamines the arguments of the advocates a border regime that would protect Slovenia as well as the European Union, not only from illegal immigrations andcriminal activities outside the Union, but also from the 'unpredictable Balkans'. On the other hand, the author focuses on understanding the changing border regimes and the roles of 'guardians of the frontier' among the 'descendants of the Uskoki'.
Keywords: Slovenia; Slovenija; Croatia; Hrvaška; obmejna območja; etnične skupine; etnični odnosi; Uskoki; Uskoks